ANALISIS IMPLEMENTASI PROGRAM SEKOLAH RAKYAT DALAM PEMENUHAN HAK ATAS PENDIDIKAN BERDASARKAN PASAL 31 UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 DI KOTA JAMBI - Nurtati Ritonga, Sri; Aditya Candra, Alif; Tiara Maulia, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The right to education is a constitutional right guaranteed by Article 31 of the 1945 Constitution of the Republic of Indonesia. However, its implementation still faces various obstacles, such as poverty and high school dropout rates, including in Jambi City. This study aims to analyze the implementation of the